Differentiation of Three Centella Species in Australia as Inferred from Morphological Characteristics, ISSR Molecular Fingerprinting and Phytochemical Composition - Alqahtani, Ali; Cho, Jun-Lae; Wong, Ka Ho; Li, Kong M.; Razmovski-Naumovski, Valentina; Li, George Q. (Frontiers in Plant Science, 2017)
Centella asiatica is one of the popular herbs used for inflammatory and neural conditions. Its differentiation from similar species is currently lacking. The aims of this study were to differentiate the three closely related Centella species using methods based on morphological characters, genetic biodiversity, phytochemical compositions and antioxidant activities. According to the morphological characteristics, the collected samples were identified as three species: C. asiatica, Centella cordifolia and Centella erecta and clustered into three groups based on their morphometric variability. Dendogram constructed on the basis of the intersimple sequence repeats (ISSR) analyses were consistent with the morphological grouping. Centella cordifolia had the highest triterpene glycosides, phenolics and antioxidant capacity, followed by C. asiatica, then C. erecta, therefore, was genetically and chemically closer to C. asiatica, while C. erecta was distinctively different from them. The results confirm the occurrence of the closely related three species of Centella in Australia, and the differentiation among them can be achieved via the combination of morphometric, molecular and phytochemical methods. This first comparative botanical study on Centella species provides a foundation for further systematic study and medicinal development of Centella.